Comparative techno-economic assessment of multi-feedstock to multi-product integrated lignocellulosic biorefinery - Semaan, Georgeio; Ozturk, Abdullah Bilal; Kumar, Gopalakrishnan (ELSEVIER, 2025)
A techno-economic assessment was performed for a multi-feedstock lignocellulosic biorefinery that converts Norwegian tomato and cucumber crop residues, spent coffee grounds, and brewers' spent grain into value-added chemicals. Scenario 1 integrates dilute oxalic-acid hydrolysis (DAH) with oxalic-acid-assisted ethanol-organosolv delignification (ORG) and co-produces ethanol, lactic acid, ethanol-organosolv lignin, furfural, 5-hydroxymethylfurfural, and electricity. Scenario 2 omits the lactic-acid train, whereas Scenario 3 employs DAH, only without the ORG or lactic acid sections. Mass and energy balance simulations informed discounted cash flow models for feedstock capacities of 25 and 250 kt/yr. At 25 kt/yr, all scenarios were unprofitable. Scaling to 250 kt/yr improved outcomes for Scenarios 1 and 3, yielding 11.5-12.6 % internal rate of return (IRR), US$ 183.7-185MM net present value (NPV). ORG inclusion reduced overall returns due to elevated capital and operating costs. Integrated operation produced negative net unit production costs, indicating internal cost crosssubsidization among co-products. Sensitivity analysis identified revenue and operating expenditures as primary determinants of NPV and IRR. Monte Carlo analysis estimated a 93.7 % probability of profitability in all simulated outcomes. The findings underscore the importance of scaling up and diversifying product portfolio in future biorefinery deployments.
Keywords: Lignocellulosic biomass; Biorefinery; Biochemicals; Pretreatment; Process simulation; Techno-economic assessment; Economic feasibility; LACTIC-ACID; BIOETHANOL PRODUCTION; CELLULOSIC ETHANOL; BIOMASS; FRACTIONATION; OPTIMIZATION; PURIFICATION; BIOPROCESS; SEPARATION; Biotechnology & Applied Microbiology; Engineering